Effect of unsaturated soil on deterministic and probabilistic analysis of the stability of an earth dam in steady state (case study: Seydon dam – Iran) - Seyed Ali Asghari Pari; Seyed Amin Asghari Pari (علوم و مهندسی آبیاری)
The stability and flow rate of earth dams are influenced by several factors, including geometric characteristics, material permeability, and the height of water upstream. To effectively understand the behavior of unsaturated soils in earth dams, it is essential to apply the principles of unsaturated soil mechanics, given the complexities involved. Neglecting uncertainties in geotechnical assessments can lead to incorrect estimates of safety factors for dam slope stability. This research investigates the impact of unsaturated soil conditions on seepage discharge and the safety factor for the downstream of the earth dam under varying scenarios, with a focus on the Seydon Dam in Khuzestan province, Iran. The findings indicate that modeling the dam's soil as a saturated-unsaturated system decreases the computed flow rate through the dam and enhances the downstream slope's safety factor in both probabilistic and deterministic analyses. Additionally, a sensitivity analysis reveals that the earth dam shell's parameters significantly influence downstream slope stability. Spatial variation analysis further indicates that accounting for spatial changes in soil parameters can decrease the safety factor of the downstream slope compared to a standard assessment.